Методика модульного навчання фізичної культури студентської молоді = The methodology of module teaching of physical culture of students - Fajdevych, Volodymyr (Journal of Education, Health and Sport, 2015)
Fajdevych Volodymyr. Методика модульного навчання фізичної культури студентської молоді = The methodology of module teaching of physical culture of students. Journal of Education, Health and Sport. 2015;5(12):377-385. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35505 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A377-385 http://pbn.nauka.gov.pl/works/682674 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 17.12.2015. УДК 37.037 Методика модульного навчання фізичної культури студентської молоді The methodology of module teaching of physical culture of students Metody nauczania modułowego wychowania fizycznego studentów Volodymyr Fajdevych Володимир Файдевич Східноєвропейський національний університет імені Лесі Українки (м. Луцьк) Lesya Ukrainka Eastern European National University (Lutsk) Анотації Однією із ключових проблем є зміна пояснювально-ілюстративного та репродуктивного видів навчання на інтенсивні технології. Така ситуація спонукає до пошуку нових, особистісно-зорієнтованих методик навчання фізичної культури студентів. Серед них центральне місце займає модульна система навчання. Основними положеннями, на яких побудована методика роботи за новою моделлю, є індивідуалізація засобів і методів навчання, підвищення обсягів та інтенсивності навчальних занять, акцентований розвиток рухових якостей і на їх основі – рухових умінь, навичок, інтересу до занять та, як наслідок, підвищення результативності педагогічного процесу Методика модульного навчання передбачає мету, завдання, принципи, засоби навчання (фізичні вправи, ігри, гігієнічні фактори, оздоровчі сили природи) навчання, методи навчання (чітко-регламентований, частково-регламентований, ігровий, змагальний, методи слова, наочні методи), форми навчання (навчальні заняття, ранкова гігієнічна гімнастика, самостійні заняття), результати навчальної діяльності, педагогічний контроль і корекцію навчального процесу. Ключові слова: студенти, модульне навчання, фізичне виховання, індивідуалізація. One of the key problems is change of explanatory-illustrative and reproductive kinds of studying with the intensive technologies. Such situation leads to searching of new, personally oriented methodologies of teaching of physical culture to students. The main principles, on which the methodology of work is built according to the new model, is individualization of means and methods of studying, increasing the amount and intensity of educational classes aimed at development of motor qualities and on their basis increasing of motor abilities, skills, interest to classes and, as a result, increasing of the effectiveness of the pedagogical process. Methodology of the module teaching foresees aim, objectives, principles, means of teaching (physical exercises, games, hygienic factors, recreational power of nature), teaching methods (precisely regulated, partially regulated, playing, competitive, verbal methods, visual methods), forms of studying (educational classes, morning hygienic gymnastics, individual trainings), results of educational activity, pedagogical control and correction of educational process. Key words: students, module teaching, physical education, individualization. Jednym z głównych problemów jest zmiana objaśniającego-ilustracyjnego i reprodukcyjnego typów edukacji na technologie intensywne. Sytuacja ta prowadzi do wyszukiwania nowych, indywidualnie zorientowanych metodyk nauczania kultury fizycznej studentów. Wśród nich centralne znaczenie ma modułowy system nauczania. Podstawowe zasady, na które opiera się metoda roboty według nowego modelu, jest indywidualizacja instrumentów i metod szkoleniowych, podniesienie objętości a intensywności zajęć, zaakcentowany rozwój zdolności motorycznych i na ich podstawie — zdolności, umiejętności motorycznych, zainteresowania do nauczania, i jako rezultat, zwiększenie skuteczności procesu edukacyjnego. Metodyka nauczania modułowego przewiduje cele, zadania, zasady, narzędzia edukacyjne (ćwiczenia fizyczne, gry, czynniki higieniczne, zdrowotne siły przyrody), metody nauczania (wyraźnie uregulowany, częściowo regulowany, zabawowy, rywalizujący, metody werbalne, metody wizualne), formy nauczania (sesje szkoleniowe, poranna gimnastyka higieniczna, zajęcia indywidualne), wyniki działalności edukacyjnej, kontrolę pedagogiczną a korygowanie procesu edukacyjnego. Słowa kluczowe: studenci, nauczanie modułowe, wychowanie fizyczne, indywidualizacja.